Nanomedicine breakthroughs in cancer and neurodegenerative disease therapy - Abdul Haque; Tariq Khan; Rayees Ul Islam; Swaleha Naseem (Next Nanotechnology)
Cancer is a significant medical concern that presents a substantial risk to the holistic health of persons. Moreover, afflictions affecting the central nervous system, including neurodegenerative disorders, offer a significant peril to the well-being of the general population and necessitate immediate scholarly focus. Brain cancer and Alzheimer's disease pose substantial treatment challenges due to the formidable task of effectively delivering medication over the protective fluid barrier of the brain. Compared to conventional medicine, nanotechnology-based treatments are more secure, effective, and selective in targeting molecular and cellular processes. The optimization of cancer treatment is an ongoing process driven by advancements in established treatment procedures and the emergence of novel therapeutic modalities. Nanomedicine plays a significant part in the progress of tumor therapy techniques. This article presents an in-depth review of the various applications of nanomedicine in the realms of chemotherapy, gene therapy, and immunotherapy. In light of prevailing challenges, including sub-optimal specificity of first-line chemotherapy agents, susceptibility of nucleic acid drugs to degradation, and frequent occurrence of negative symptoms associated with the immune system in immunotherapy, this discourse explores the potential integration of nanomedicine with these therapeutic approaches. The discussion encompasses illustrative instances and highlights the benefits associated with using nanomedicine.